One decade of quantum optimal control in the chopped random basis. (1st July 2022) - Müller, Matthias M; Said, Ressa S; Jelezko, Fedor; Calarco, Tommaso; Montangero, Simone
Abstract: The chopped random basis (CRAB) ansatz for quantum optimal control has been proven to be a versatile tool to enable quantum technology applications such as quantum computing, quantum simulation, quantum sensing, and quantum communication. Its capability to encompass experimental constraints—while maintaining an access to the usually trap-free control landscape—and to switch from open-loop to closed-loop optimization (including with remote access—or RedCRAB) is contributing to the development of quantum technology on many different physical platforms. In this review article we present the development, the theoretical basis and the toolbox for this optimization algorithm, as well as an overview of the broad range of different theoretical and experimental applications that exploit this powerful technique.